The effect of variation in inter-appointment time on the incidence of post-operative pain in single-visit versus two visit endodontics: An in vivo study - Sumita A Bhagwat; Aditi Patel; Lalitagauri P Mandke (Wolters Kluwer Medknow Publications, 2012)
Aim: This clinical study was conducted to observe and note the effect of variation in inter-appointment time period on the incidence of post-operative pain following single-visit versus two visit endodontics in vital and nonvital teeth with and without periapical radiolucency. Materials and Methods: A total of 80 adult patients requiring root canal therapy in anterior and premolar teeth were selected for this study and divided into four groups. Two sitting root canal treatment was carried out in three groups (Group 1 with inter-appointment time of 72 h, Group 2 with inter-appointment time of 48 h and Group 3 with inter-appointment time of 24 h) and single sitting root canal treatment was carried out in one group (Group 4). The subjects were recalled after 2 weeks and instructed to fill out a series of self-report questionnaires for responses about pain in the interim after 1 day, 2 day, 3 day, 1 week and 2 weeks. Results: Though comparison of pain incidence in different groups was not statistically significant, there was a greater tendency for post obturation pain incidence in teeth treated with single sitting root canal therapy and those with inter appointment period of 72 h. Results obtained were comparable to those obtained by several investigators.